2021
DOI: 10.1016/j.ajem.2021.06.075
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of cardiac markers in the prognosis of COVID-19 in children

Abstract: Background and aim Occasionally, children with COVID-19 may develop arrhythmia, myocarditis, and cardiogenic shock involving multisystemic inflammatory syndrome in children (MIS-C). This study aimed to identify the laboratory parameters that may predict early cardiovascular involvement in these patients. Materials and methods Data of 320 pediatric patients, aged 0–18 years (average age, 10.46 ± 5.77 years; 156 female), with positive COVID-19 reverse transcription–polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
1
19
1
Order By: Relevance
“…COVID-19 presents primarily with pulmonary disease; however, especially in adults, a significant portion of patients have cardiac involvement [ 2 4 ]. Like adults, children can have cardiac involvements such as arrhythmia, myocarditis, and cardiogenic shock with MIS-C associated with SARS-CoV-2 infection [ 7 , 8 ]. The pathogenesis of the cardiac damage of COVID-19 is not clear in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…COVID-19 presents primarily with pulmonary disease; however, especially in adults, a significant portion of patients have cardiac involvement [ 2 4 ]. Like adults, children can have cardiac involvements such as arrhythmia, myocarditis, and cardiogenic shock with MIS-C associated with SARS-CoV-2 infection [ 7 , 8 ]. The pathogenesis of the cardiac damage of COVID-19 is not clear in children.…”
Section: Discussionmentioning
confidence: 99%
“…Güllü et al [ 8 ] evaluated 320 pediatric patients, and five were diagnosed with MIS-C. They reported that cardiac markers (NT-proBNP and troponin I), especially NT-proBNP, could be used to detect early diagnosis of cardiac involvement and/or MIS-C in pediatric patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Troponin is a protein released into the bloodstream following cell damage and is used as a marker of myocardial damage due to its cardiac specificity. Elevated troponin was also found to be associated with severe illness and poor prognosis for pediatric COVID-19 and MIS-C. 24,25 Based on this information, although we detected no cardiac dysfunction in our own patient group in clinical examination or echocardiography, we accepted troponin elevation as a marker of cardiac involvement. Therefore, we compared RDW in patients with and without troponin elevation and our statistical evaluation revealed a positive correlation between high RDW and elevated troponin levels.…”
Section: Resultsmentioning
confidence: 55%
“…Recently, studies with brain natriuretic peptide (BNP) have started to gain importance in terms of human physiology [ 4 ]. BNP is widely used as a biomarker in heart diseases.…”
Section: Introductionmentioning
confidence: 99%